Quantity rationing of credit - George A. Waters (Bank of Finland, 2012)
Quantity rationing of credit, when firms are denied loans, has greater potential to explain macroeconomics fluctuations than borrowing costs. This paper develops a DSGE model with both types of financial frictions. A deterioration in credit market confidence leads to a temporary change in the interest rate, but a persistent change in the fraction of firms receiving financing, which leads to a persistent fall in real activity. Empirical evidence confirms that credit market confidence, measured by the survey of loan officers, is a significant leading indicator for capacity utilization and output, while borrowing costs, measured by interest rate spreads, is not.
URN:NBN:fi:bof-20140807549
Keywords: E10; E24; E44; E50; 330; quantity rationing; credit; VAR